Peran Customer Satisfaction Memediasi Pengaruh E-Service Quality Terhadap Repurchase Intention - I Gede Nandikha Arsa Wibawa; Ni Made Rastini (Parsimonia - Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of customer satisfaction in mediating the effect of e-service quality on repurchase intention among Fore Coffee customers in Denpasar City. The background of this research is the increasingly intense competition in the application-based coffee shop business and the need for Fore Coffee to improve its digital service quality to retain customers. The variables used in this study include e-service quality (X) as the independent variable, customer satisfaction (M) as the mediating variable, and repurchase intention (Y) as the dependent variable. The population of this study consists of all Fore Coffee customers in Denpasar City who make purchases more than twice a month through the Fore Coffee application. The sampling technique used was purposive sampling with a total of 120 respondents. Data were collected using questionnaires and analyzed using path analysis, complemented by the Sobel test to examine the mediating effect.The results of the study show that (1) e-service quality has a positive and significant effect on repurchase intention, (2) e-service quality has a positive and significant effect on customer satisfaction, (3) customer satisfaction has a positive and significant effect on repurchase intention, and (4) customer satisfaction significantly mediates the effect of e-service quality on repurchase intention. These findings indicate that good digital service quality not only directly encourages repurchase intention but also does so indirectly through increased customer satisfaction. The implication of this research is the importance for Fore Coffee to maintain service aspects that have been rated positively by customers, such as responsiveness and customer service support, while improving application design and transaction security. This research also provides theoretical contributions by strengthening the model of the relationship between e-service quality, customer satisfaction, and repurchase intention in the context of application-based services in the coffee shop industry.